Promotive And Preventive Approach As A Health Development Strategy - Syaiful Bachri; Rahmat Pannyiwi; Anggeraeni Anggeraeni (International Journal of Health Sciences, 2026)
The promotive and preventive approach is a primary strategy in health development, aimed at improving public health and reducing morbidity and mortality. This approach emphasizes efforts to increase knowledge, attitudes, and healthy living behaviors, as well as preventing disease before it occurs. This study aims to analyze the role of the promotive and preventive approach as a health development strategy. The study used quantitative methods with a descriptive analytical design and a cross-sectional approach. Sectional. The research sample was the community in region X. Data were collected using questionnaires and analyzed univariately and bivariately using the Chi- Square test. The results showed that the implementation of a good promotive and preventive approach was significantly related to community health status (p < 0.05). The conclusion of this study is that promotive and preventive approaches have a strategic role in supporting sustainable health development.